Therapeutic exploitation of IPSE, a urogenital parasite‐derived host modulatory protein, for chemotherapy‐induced hemorrhagic cystitis. Issue 8 (3rd April 2018) - Mbanefo, Evaristus C.; Le, Loc; Pennington, Luke F.; Odegaard, Justin I.; Jardetzky, Theodore S.; Alouffi, Abdulaziz; Falcone, Franco H.; Hsieh, Michael H.
Abstract : Chemotherapy‐induced hemorrhagic cystitis (CHC) can be difficult to manage. Prior work suggests that IL‐4 alleviates ifosfamide‐induced hemorrhagic cystitis (IHC), but systemically administered IL‐4 causes significant side effects. We hypothesized that the Schistosoma hematobium homolog of IL‐4‐inducing principle from Schistosoma mansoni eggs (H‐IPSE), would reduce IHC and associated bladder pathology. IPSE binds IgE on basophils and mast cells, triggering IL‐4 secretion by these cells. IPSE is also an "infiltrin, " translocating into the host nucleus to modulate gene transcription. Mice were administered IL‐4, H‐IPSE protein or its nuclear localization sequence (NLS) mutant, with or without neutralizing anti‐IL‐4 antibody, or 2‐mercaptoethane sulfonate sodium (MESNA; a drug used to prevent IHC), followed by ifosfamide. Bladder tissue damage and hemoglobin content were measured. Spontaneous and evoked pain, urinary frequency, and bladdergene expression analysis were assessed. Pain behaviors were interpreted in a blinded fashion. One dose of H‐IPSE was superior to MESNA and IL‐4 in suppressing bladder hemorrhage in an IL‐4‐dependent fashion and comparable with MESNA in dampening ifosfamide‐triggered pain behaviors in an NLS‐dependent manner. H‐IPSE also accelerated urothelial repair following IHC. Our work represents the first therapeutic exploitation of a uropathogen‐derived host modulatory molecule in a clinically relevant bladder disease model and indicates that IPSE may be an alternative to MESNA for mitigating CHC.—Mbanefo, E. C., Le, L., Pennington, L. F., Odegaard, J. I., Jardetzky, T. S., Alouffi, A., Falcone, F. H., Hsieh, M. H. Therapeutic exploitation of IPSE, a urogenital parasite‐derived host modulatory protein, for chemotherapy‐induced hemorrhagic cystitis. FASEB J . 32, 4408–4419 (2018). www.fasebj.org